Multi-omic analysis identifies erythroid cells as the major population in mouse placentas expressing genes for antigen presentation in MHC class II, chemokines, and antibacterial immune response - Perik-Zavodskaia, Olga; Perik-Zavodskii, Roman; Alrhmoun, Saleh; Nazarov, Kirill; Shevchenko, Julia; Zaitsev, Konstantin; Sennikov, Sergey (Frontiers in Immunology, 2025)
IntroductionPregnancy is a complex process that requires a tightly regulated immune environment to support fetal development and protect against infections. The main barrier between fetus and mother is a specialized organ, the placenta, where the role of specific immune cell populations remains incompletely understood.MethodsIn this work, we used spatial transcriptomics at E12.5 to characterize immune and non-immune cell heterogeneity and spatial organization in the mouse placenta. In addition, we performed murine placental mononuclear cell flow cytometry proteomics, murine placental erythroid cell NanoString bulk transcriptomics, and murine placental erythroid cell LegendPlex secretomics at E12.5 and E19.5 to further analyze the immune landscape in the mouse placenta. We also performed single-cell RNA sequencing of human cord blood erythroid cells for cross-species comparisons.ResultsOur results show that erythroid cells constitute the predominant immunoregulatory population in murine placentas, comprising on average 80% and 40% of the placental mononuclear cells at E12.5 and E19.5, respectively, expressing Ctss, Cd74, H2-Aa, and H2-Ab1 genes involved in antigen presentation via MHC-II, and a PD-L1 checkpoint inhibition molecule gene expression. They also have gene expression of such immunomodulatory molecules as Tgfb1 and Tgfb3 cytokines, Ccl2, Ccl3, Ccl4, Ccl9, Cxcl1, Cxcl12, and Mif chemokines, and antimicrobial protein calprotectin S100a8, S100a9 genes.DiscussionThese results indicate that erythroid cells may act as potent regulators of immunity in murine placentas due to their vast number and repertoire of immunoregulatory molecules, shaping the immune landscape through diverse immunoregulatory mechanisms.